2007
DOI: 10.1002/aic.11393
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of foaming on polymer‐paperboard composites

Abstract: in Wiley InterScience (www.interscience.wiley.com).Foamed paperboard is a composite material with applications in the consumer products industry. The composite is comprised of paperboard sandwiched between two layers of polymers. One layer foams upon heating while the other acts as a barrier layer. Foaming is caused by the vaporization of the small amount of moisture present in the board and the resulting increase in pressure. The mechanism of foaming was investigated with a combination of high-speed photograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…We have previously shown that heating the paperboard–polymer composite initially leads to the formation of a large number of small bubbles 2. These then grow, collapse, or coalesce so that the bubble count decreases after an initial spike.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that heating the paperboard–polymer composite initially leads to the formation of a large number of small bubbles 2. These then grow, collapse, or coalesce so that the bubble count decreases after an initial spike.…”
Section: Resultsmentioning
confidence: 99%
“…These then grow, collapse, or coalesce so that the bubble count decreases after an initial spike. The manner in which the board is constructed affects the pore structure of the sheet and, therefore, the number and geometry of the bubbles formed 2. The polymer is integral to the foaming process and must play a role in the growth of the foam.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations